The evolution of the use of mathematics in cancer research - Gutierrez Diez, Pedro J. (Springer US, 2012)
This book is designed for advanced students and researchers pursuing the use of biostatistics and biomathematics in their investigations in biology and medicine in general, and in cancer in particular. Each chapter has been conceived as a part in the whole in such a way that information flows easily, explaining in a concise and clear way a particular subject, and connecting its results with those in the previous and following chapters. State-of-the-art biostatistics and biomathematics methods and techniques are explained in detail through illustrative and capital examples taken from cancer research work already published, and the result is a self-contained book on medicine, statistics and mathematics which illustrates the potential of biostatistics and biomathematics in biomedical research. Focusing on the achievements that biostatistics and biomathematics have already obtained, researchers can perceive the high returns that the use of statistics and mathematics yield in biomedical research, and thanks to the detailed discussion of the applied statistical and mathematical techniques, they can deduce the criteria and motif for finding the appropriate use of these formal disciplines.